EFFECT OF DILUTORS ON MOTILITY, MORPHOLOGY AND ACROSOME INTEGRITY OF RAM SPERMATOZOA DURING FREEZING - NEMA, s p; SUTHAR, B N; KAVANl, F S; DHAMl, A J (The Indian Journal of Animal Reproduction, 2023)
The effects of dilutors, rams, stages of freezing process and their interactions were studied in 90 ejaculatesin a 3x5x3 factorial experiment for biophysical characteristics of sperms during freezing of sheep semen. Thediluents used was 20% egg yolk and 4% glycerol with tris fructose citric acid. (TFCEG), a synthetic phosphatemedium (Phos) and sodium citrate glucose egg yolk glycerol (SCGEG). The influences of dilutors, rams, stagesof freezing and interactions of dilutor with ram, and dilutorwith stages of freezing were highly significant (P
Keywords: Dilutors; Freezability; Motility; Morphology; Acrosome integrity; Ram semen